Applications of generalized fractional integral operator to unified subclass of prestarlike functions with negative coefficients - JOSHI, Santosh B.; JOSHI, Sayali S.; PAWAR, Haridas (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper, we have introduced and studied various properties of unified class of prestarlike functions with negative coefficients in the unit disc U . Also distortion theorem involving a generalized fractional integral operator for functions in this class is established. Mathematics Subject Classification (2010): 30C45.